Deposition of high hardness coating by low power atmospheric pressure microwave plasma spray and the characteristics evaluations - Ahmad Redza, Ahmad Mokhtar (2012)
Atmospheric microwave discharge easily generates plasma at a microwave power of not more than 1kw. Low power atmospheric pressure plasma spraying expects promising way to deposit coatings with reduced micro structural change. In the research findings, we investigated that by 1.0kW of input power, it is possible to generate about 4000 K plasma for the deposition of metal and ceramics coatings by microwave plasma spray. Moreover, low power atmospheric pressure microwave plasma spray is also expected as a promising way to deposit coatings onto heat susceptible substrates such as high carbon steel and CFRP (carbon fiber reinforced plastic). In this research, low power microwave plasma spraying system under the atmospheric pressure was studied. The substrate temperature during spraying, particle velocity and the thermal efficiency of plasma was measured as the operational characteristics of the system. Furthermore, high hardness coatings were deposited with metallic (Cr) and ceramics (Al203) materials onto heat susceptible substrates. The characteristics of the coatings obtained by this research were evaluated.